Pharmacotherapeutic management of insomnia and effects on sleep processes, neural plasticity, and brain systems modulating stress: A narrative review - Palagini, Laura; Bianchini, Carlotta (Frontiers in Neuroscience, 2022)
Introduction Insomnia is a stress-related sleep disorder, may favor a state of allostatic overload impairing brain neuroplasticity, stress immune and endocrine pathways, and may contribute to mental and physical disorders. In this framework, assessing and targeting insomnia is of importance. Aim Since maladaptive neuroplasticity and allostatic overload are hypothesized to be related to GABAergic alterations, compounds targeting GABA may play a key role. Accordingly, the aim of this review was to discuss the effect of GABAA receptor agonists, short-medium acting hypnotic benzodiazepines and the so called Z-drugs, at a molecular level. Method Literature searches were done according to PRISMA guidelines. Several combinations of terms were used such as “hypnotic benzodiazepines” or “brotizolam,” or “lormetazepam” or “temazepam” or “triazolam” or “zolpidem” or “zopiclone” or “zaleplon” or “eszopiclone” and “insomnia” and “effects on sleep” and “effect on brain plasticity” and “effect on stress system”. Given the complexity and heterogeneity of existing literature, we ended up with a narrative review. Results Among short-medium acting compounds, triazolam has been the most studied and may regulate the stress system at central and peripheral levels. Among Z-drugs eszopiclone may regulate the stress system. Some compounds may produce more “physiological” sleep such as brotizolam, triazolam, and eszopiclone and probably may not impair sleep processes and related neural plasticity. In particular, triazolam, eszopiclone, and zaleplon studied in vivo in animal models did not alter neuroplasticity. Conclusion Current models of insomnia may lead us to revise the way in which we use hypnotic compounds in clinical practice. Specifically, compounds should target sleep processes, the stress system, and sustain neural plasticity. In this framework, among the short/medium acting hypnotic benzodiazepines, triazolam has been the most studied compound while among the Z-drugs eszopiclone has demonstrated interesting effects. Both offer potential new insight for treating insomnia.